Chlorination of RuO2 with gaseous Cl2 between 998 and 1123 K - Bohe, Ana Ester (2015)
Employing methods of separation based on selective chlorination it is possible to separate valuable components, such as metals and rare earths, from ores and / or solid wastes. In this paper we study the chlorination reaction of ruthenium oxide. This element is among nuclear fission products, also part of many electronic wastes and numerous catalysts in the chemical industry. The study of the chlorination reaction of ruthenium oxide will allow to analyze in which conditions it is possible to apply gaseous chlorination for ruthenium recovery. No systematic studies on the kinetics and chemical mechanism of ruthenium oxide chlorination are available in the literature. In the present study, we performed a thermodynamic analysis of possible reaction pathways. The reaction products were identified by scanning electron microscopy (SEM) and x-ray Diffraction (xrd), and the experimental conditions for obtaining stable α-RuCl3 by RuO2 chlorination and subsequent heating in Cl2 were established. The starting temperature for the chlorination was determined at 983 K. The observed mass loss is due to formation of volatile products. We analyzed the effects of gas flow rate, crucible geometry, and sample mass on the kinetics of the reaction, in order to establish the corresponding experimental reaction conditions for chemical kinetic control. The effect of temperature was analyzed and an apparent activation energy of 173 ± 8 kJ.mol-1 was obtained for the chlorination reaction.